EVALUATING THE BUSINESS VIABILITY OF SUSTAINABLE TRANSPORTATION INITIATIVES: A CASE STUDY OF GREEN LOGISTICS IMPLEMENTATION - I Made Suraharta; Nico Djajasinga; Luluk Fauziah; Sri Umiatun Andayani; Mashudi Mashudi (UIN Sunan Gunung Djati Bandung, 2023)
Transportation is an important part of this era of globalization. But at the same time transportation, especially in the field of logistics, often harms the environment. This research will then look at the impact of sustainable transportation and the implementation of green logistics on the environment. This research will be carried out using a descriptive qualitative approach. The data used in this study comes from various relevant previous research results or studies. The results of this study then found that the negative impact of conventional transportation led to the importance of changes in transportation management. Through the adoption of innovative technology, smart route management, and environmentally friendly vehicles, a company will be able to reduce operational costs, increase efficiency, and significantly reduce the negative impact it has on the environment. Sustainable transportation and green logistics are strategic opportunities for future businesses.